The effect of learning strategies and reflex movements on 10-finger typing skills of Medan aviation polytechnic cadets - Amril, Muhammad; Anwar, Syairi; Margolang, Julfansyah; Sunardi, Sunardi (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this research is to determine whether the typing skills of cadets trained using plus tone software are better than those using software alone, whether the typing skills of cadets who have high reflex movements are better than those who have low reflex movements, and whether there is an interaction between the use of 10-finger typing training software and reflex movements in influencing typing skills. The population of the study was the Air Traffic Control Department Cadets at the Medan Aviation Polytechnic, Indonesia. The sampling technique in this study was a random group sampling technique (cluster random sampling), namely 4 Classes 2 classes were selected as samples that were given treatment through random selection. The analysis technique was a two-way ANOVA at a significance level of 0.05 which was continued with the Scheffe test. The results of the study were : (a) The average learning outcomes of typing skills of cadets taught with fixed rhythm software ( = 94.82) were higher than the average learning outcomes of typing skills of cadets taught with fixed rhythm software ( = 93.12) with F count = 11.09 > F table = 4,004, (b ) The average learning outcomes of typing skills for cadets with high reflex motor abilities ( = 94.82) are higher than the learning outcomes of typing skills for cadets with low reflex motor abilities ( = 93.11), with F count = 8.84 > F table = 4,004, and (c ) there is an interaction between learning strategies and reflex motor abilities on learning outcomes of typing skills with F count = 5.49 > F table = 4.004. The results of the data analysis concluded that for cadets with high reflex movement ability characteristics, the appropriate learning strategy used is fixed rhythm software. For cadets with low reflex movement ability characteristics, the appropriate learning strategy used is software only. The implications of this study are specifically aimed at the Indonesian Ministry of Transportation and teaching staff.